Combining culture optimization and synthetic biology to improve production and detection of secondary metabolites in Myxococcus xanthus: application to myxoprincomide - Mathieu Sourice; Charlotte Simmler; Marc Maresca; Béatrice Py; Corinne Aubert (Microbiology Spectrum)
ABSTRACT Microbial secondary metabolites play crucial ecological roles in governing species interactions and contributing to their defense strategies. Their unique structures and potent bioactivities have been key in discovering antibiotics and anticancer drugs. Genome sequencing has undoubtedly revealed that myxobacteria constitute a huge reservoir of secondary metabolites as the well-known producers, actinomycetes. However, because most secondary metabolites are not produced in the laboratory context, the natural products from myxobacteria characterized to date represent only the tip of the iceberg. By combining the engineering of a dedicated Myxococcus xanthus DZ2 chassis strain with a two-step growth medium protocol, we provide a new approach called two-step Protocol for Resource Integration and Maximization–Biomolecules Overproduction and Optimal Screening Therapeutics (2PRIM-BOOST) for the production of non-ribosomal peptides synthetases (NRPS)/polyketides synthases (PKS) secondary metabolites from myxobacteria. We further show that the 2PRIM-BOOST strategy will facilitate the screening of secondary metabolites for biological activities of medical interest. As proof of concept, using a constitutive strong promoter, the myxoprincomide from M. xanthus DZ2 has been efficiently produced and its biosynthesis has been enhanced using the 2PRIM-BOOST approach, allowing the identification of new features of myxoprincomide. This strategy should allow the chances to produce and discover new NRPS, PKS, and mixed NRPS/PKS hybrid natural metabolites that are currently considered as cryptic and are the most represented in myxobacteria.IMPORTANCEMicrobial secondary metabolites are important in species interactions and are also a prolific source of drugs. Myxobacteria are ubiquitous soil-dwelling bacteria constituting a huge reservoir of secondary metabolites. However, because most of these molecules are not produced in the laboratory context, one can estimate that only one-tenth have been characterized to date. Here, we developed a new strategy called two-step Protocol for Resource Integration and Maximization–Biomolecules Overproduction and Optimal Screening Therapeutics (2PRIM-BOOST) that combines the engineering of a dedicated Myxococcus xanthus chassis strain together with growth medium optimization. By combining these strategies with the insertion of a constitutive promoter upstream the biosynthetic gene cluster (BGC), the production of myxoprincomide, a characterized low-produced secondary metabolite, was successfully and significantly increased. The 2PRIM-BOOST enriches the toolbox used to produce previously cryptic metabolites, unveil their ecological role, and provide new molecules of medical interest.